Increasing productivity in high speed machining of Ti-6Al-4V alloy under high pressure coolant supply. (30th May 2007) - Da Silva, Rosemar Batista; Machado, Alisson Rocha; Ezugwu, Emmanuel Okechukwu; Bonney, John
Cemented carbide tools are the most common tool materials employed in the machining of titanium alloys. Polycrystalline Diamond (PCD) tools can substantially enhance the machining productivity. So, this study investigates the performance of PCD tools when machining Ti-6Al-4V alloy at cutting speeds up to 250 m min-1 with coolant delivered under pressures. The results show that longer tool life can be achieved when machining with high pressure coolant supplies up to 20.3 MPa compared with the conventional coolant flow. Up to three folds increase in cutting speed can be achieved when machining with uncoated cemented carbide tools relative to that currently used for manufacture in industry, while with PCD tools, up to five fold increase in cutting speed is achievable when machining with PCD tools.